2020
DOI: 10.3389/fmicb.2020.541554
|View full text |Cite
|
Sign up to set email alerts
|

An Improved hgcAB Primer Set and Direct High-Throughput Sequencing Expand Hg-Methylator Diversity in Nature

Abstract: The gene pair hgcAB is essential for microbial mercury methylation. Our understanding of its abundance and diversity in nature is rapidly evolving. In this study we developed a new broad-range primer set for hgcAB , plus an expanded hgcAB reference library, and used these to characterize Hg-methylating communities from diverse environments. We applied this new Hg-methylator database to assign taxonomy to hgcA sequences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 94 publications
1
46
0
Order By: Relevance
“…While hgcAB has been reported in Bacteria, it has also been found in multiple Archaea (including the gut commensal, M. luminyensis ) ( Parks et al, 2013 ), and thus some potentially important microbes, relevant to Hg metabolism, were not likely represented in the sequence dataset. There was an insufficient mass of remaining fecal sample for analyses of the hgcAB gene cluster ( Gionfriddo et al, 2020 ) or MeHg demethylation ( Lu et al, 2016 ); however, these assays will be included in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…While hgcAB has been reported in Bacteria, it has also been found in multiple Archaea (including the gut commensal, M. luminyensis ) ( Parks et al, 2013 ), and thus some potentially important microbes, relevant to Hg metabolism, were not likely represented in the sequence dataset. There was an insufficient mass of remaining fecal sample for analyses of the hgcAB gene cluster ( Gionfriddo et al, 2020 ) or MeHg demethylation ( Lu et al, 2016 ); however, these assays will be included in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a combination of methylation assays using metabolic inhibitors and molecular genetic surveys of microbial assemblages broadened the diversity of putative Hg methylators to include iron-reducing bacteria (FeRB) (15) and methanogens (16). The discovery of the genetic basis for Hg methylation (hgcA and hgcB genes that encode a corrinoid iron-sulfur protein and a ferredoxin protein, respectively) (17) has facilitated studies that have expanded the diversity of putative Hg methylators and explored their distributions in the environment (18)(19)(20)(21)(22). Numerous additional bacterial phyla are now known to be implicated in MMHg production, including Actinobacteria, Bacteroidetes, Firmicutes, and Chloroflexi (17,18,(23)(24)(25).…”
mentioning
confidence: 99%
“…The bacterial phylum Proteobacteria has previously been found to dominate periphyton ( Bae et al, 2019 ) but not Atribacteria. Sediment samples collected from the same study site (EFPC) also found an abundance of Proteobacteria, but rather than Candidatus Atribacteria, the sediment community had an abundance of Nitrospirae and Chloroflexi that dominated the Hg-methylating community ( Gionfriddo et al, 2020 ) Candidatus Atribacteria are a ubiquitous and difficult to cultivate phylum ( Katayama et al, 2020 ). Given the vast interaction networks the periphyton microbiome demonstrated, networks of the periphyton may aid in future isolation endeavors of these taxa as well as other difficult-to-cultivate microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…After extraction, a two-step PCR approach was used with barcode tagged templates and primers targeting the V4 region of the 16S rRNA gene for archaea and bacteria and the ITS2 region of the ribosomal operon for fungi using pooled primer sets ( Supplementary Table S1 ) to increase coverage of archaeal, bacterial, and fungal marker genes ( Cregger et al, 2018 ). Hg methylation genes ( hgcAB ) were amplified with a two-step PCR following methods and primers ( Supplementary Table S1 ) previously described ( Gionfriddo et al, 2020 ). After PCRs, all experimental units were pooled equally and purified with Agencourt AMPure XP beads (0.7:1 bead-to-DNA ratio; Beckman Coulter Inc., Pasadena, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation